Study of clinical presentations of lung cancer in tertiary level hospital - Jadhav, Sharad; Handa, Ajay; Kumar, Sharwan; Chowdhury, G. S. (International Journal of Advances in Medicine, 2022)
Background: Lung cancer is the most common cancer diagnosed worldwide. It is also the leading contributor to cancer-related mortality, resulting in around 1.38 million cancer deaths per year worldwide. The aim and objective of the study was to study the clinical presentations including paraneoplastic manifestations and metastatic effects of lung cancer and to identify reasons for delay in diagnosis of lung cancer. Methods: Hospital based observational study was conducted on 100 consecutive cases. Results: Mean age of the cases with lung cancer was 56.36 years and 30% of the cases. Male predominance was seen with 63% males to 37% females. Tobacco smoking was present in 59% cases while exposure to second hand smoke and biomass fuel was seen in 11% and 9% patients. Most common presenting symptoms were cough (22.21%), chest pain (16.13%), fever (14.37%), dyspnea (11%) and hemoptysis (5.22%). Most common type of lung tumor was Adenocarcinoma (53%) followed by Small cell carcinoma (22%) and Squamous cell carcinoma (19%). Mutation analysis by molecular testing where possible in 76.66% NSCLC cases and showed with RAS (26.19%), EGFR (23.8%), ALK1 (11.9%) and ROS (4.7%) mutation. Stage I and II of lung cancer was seen in 17% cases while stage III and IV was seen in 39% and 44% cases respectively. Conclusions: Present study shown tobacco smoking as the most common risk factor in the causation of lung cancer (59%) followed by passive smoking (11%) and biomass fuel exposure (9%). Mortality in the present study was 72% in 2 years of follow up and Median survival in the study was 11 months. We recommend high index of suspicion in the high-risk groups as smokers and those with chronic respiratory diseases to avoid delay in diagnosis.